Temporal variations of human and animal Rotavirus A genotypes in surface water used for drinking water production - Miura, Takayuki; Kadoya, Syun-suke; Takino, Hiroyuki; Sano, Daisuke; Akiba, Michihiro (Frontiers in Microbiology, 2022)
Rotavirus is a major cause of gastroenteritis among infants and children. In this study, nested PCR assays were developed to amplify partial regions of the VP7, VP4, and VP6 genes of Rotavirus A (RVA) for amplicon-based Illumina MiSeq sequencing to investigate RVA genotypes in environmental water samples. Eight sets of inner primers were first designed and screened for use in the nested PCR assays, and four sets of them could produce amplicons. Six sets of outer primers were then designed and combined with the four sets of inner primers that worked. The assays were evaluated for sensitivity using raw water samples collected from one drinking water treatment plant (DWTP) between April 2019 and March 2020 (Sample Set 1; N = 12) and seven DWTPs between 2018 and 2020 (Sample Set 2; N = 18). In total, 43 amplicons from Set 1 were sequenced and diverse sequences from human, porcine, bovine, equine, and feline RVA were observed. Human G8, G3, and G2 genotypes were obtained, with G8 predominant (relative abundance, 36−87 %) in samples taken during the rotavirus epidemic season between April and June. Porcine G5, G11, and G4, and bovine G10 and G6 genotypes were also detected. VP4 sequence analysis revealed that the human P[8] genotype was present throughout the year, whereas P[4] and P[9] were present only in the epidemic season. The vaccine strains P[5] and P[8] (RotaTeq®) were also detected. Our approach enables the identification of prevalent human and animal RVA genotypes and their host species that potentially caused fecal contamination in water sources.